2019
DOI: 10.1093/ehjcr/ytz154
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of stiff left atrial syndrome caused by both coconut left atrium and vertebral compression: a case report

Abstract: Background Calcification of the left atrium (LA) is a rare condition and can be the result of long-standing rheumatic mitral stenosis or an unusual complication after mitral valve replacement. Cases of massive LA calcification have sometimes been referred to as those with ‘coconut LA’ or ‘porcelain LA’. Case summary A 75-year-old woman was referred to our hospital because of chest discomfort and exertional dyspnoea. Doppler e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Stiff LA syndrome is defined as the combination of LA reservoir dysfunction and heart failure symptoms. Atrial fibrillation, catheter ablation, and left ventricular diastolic dysfunction reportedly contribute to its pathogenesis (6)(7)(8). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Stiff LA syndrome is defined as the combination of LA reservoir dysfunction and heart failure symptoms. Atrial fibrillation, catheter ablation, and left ventricular diastolic dysfunction reportedly contribute to its pathogenesis (6)(7)(8). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present a detailed time course of RFCA‐associated PV calcification process for the first time. It is known that progressive calcification has the potential to reduce the function of the LA as a reservoir or booster pump 5 . Because RFCA‐associated PV calcification may progress over time even with a single ablation, long‐term caution should be paid in cases of especially extensive ablation and/or patients with stiff LA syndrome.…”
Section: Figurementioning
confidence: 99%
“…In fact, despite the significant decrease in the national prevalence of rheumatic fever (RF), left atrial calcification remains a relatively common finding on imaging, both on chest and cardiac computed tomography [2,3]. Importantly, the body of literature gives other possible causes of left atrial calcification, including mitral valve disease and mitral valve replacement, end-stage renal disease, history of radiation therapy, and non-specific endocarditis, but no study has demonstrated modern distribution of pathology [4][5][6][7][8][9][10][11][12]. Indeed, the modern proliferation of endomyocardial ablation techniques and catheter-directed therapies for structural heart disease, raises the question of iatrogenic damage [13,14].…”
Section: Introductionmentioning
confidence: 99%